Answer:
Options (A) and (C)
Step-by-step explanation:
A). The given inequality is,
x + y ≤ 2
Solution area of the inequality is the shaded area below the line.
Since (0, 0) lies in the shaded region, ordered pair will be a solution of this inequality.
B). For the inequality y ≤ ![\frac{3}{2}x-1](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7Dx-1)
Since, (0, 0) doesn't lie in the shaded region of this inequality, ordered pair will not be a solution of the inequality.
C). y > ![-\frac{1}{3}x-2](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B3%7Dx-2)
In this graph (0, 0) lies in the shaded region of the inequality therefore, it will be a solution of the given inequality.
Therefore, Options (A) and (C) are the correct options.
Answer:
think one
Step-by-step explanation:
DO IT USING THINK ONE
The rule for g(x) is: ![f(x) = (x-3)^2-3](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-3%29%5E2-3)
Step-by-step explanation:
Given function is:
![f(x) = x^2](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E2)
When a function f(x) is shifted right or left, b units the new function is written as:
![f(x) = x](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x)
Shifting right
![g(x) = f(x-b)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x-b%29)
Shifting left
![g(x) = f(x+b)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x%2Bb%29)
Similarly, when shifting up or down
![g(x) = f(x)+b => Up\\g(x) = f(x) - b => Down](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x%29%2Bb%20%3D%3E%20Up%5C%5Cg%28x%29%20%3D%20f%28x%29%20-%20b%20%3D%3E%20Down)
As our given function is shifted 3 units to the right, it will be written as:
![f(x) = (x-3)^2](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-3%29%5E2)
The function is when moved down 3 units, then
![f(x) = (x-3)^2-3](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-3%29%5E2-3)
Hence
The rule for g(x) is: ![f(x) = (x-3)^2-3](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-3%29%5E2-3)
Keywords: Function transformation, Functions
Learn more about functions at:
#LearnwithBrainly
Answer:
True
Step-by-step explanation: